The main problems and conditions between state authorities and municipal administrations in Russia and foreign countries - A. V. Langinen (Путеводитель предпринимателя, 2020)
The article highlights basic legal, administrative, organizational, financial and social conditions and problems of interaction between the state and the municipal authorities of the Russian Federation andforeign states. Most significantfactors reform of local government in the modern state.